Integration and participation of older persons in socio-economic development of Harare Metropolitan Province. - Kunaka, Bothwell Gweshe (Midlands State University., 2017)
The research examined the integration and participation of the elderly in the socio-economic development of Harare Metropolitan Province (HMP). It targeted religious denominations, industry and commerce, non-governmental organizations, tertiary institutions, state enterprises and parastatals and a local authority. The research identified serious stigmatization of Old Persons (OPs), leading to their ostracism by HMP institutions in particular, and ordinary citizens in general. The less sophisticated (OPs) opted to go into Old People‟s Homes following malicious accusations, threats and persecution by and from society. The Mixed Research Method was used; questionnaires and interviews were the major data collection instruments. Respondents were afforded the opportunity to contribute additional information over and above the information solicited for by both the questionnaire and the interview guide.The major study findings were that HMP institutions did not have activities that integrated and facilitated the participation of OPs in the socio-economic development of the province. Concrete recommendations and further areas of future research are proffered in detail.